Integrasi Model Roman Jakobson dalam Pembelajaran Ilmu Ma'ani: Pendekatan Kontekstual - Budiriyanto, Anis; Putra, Sudarmadi; Romadhon, Farkhan Nur; Winanto, Edy; Widodo, Joko (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This article discusses the integration of Roman Jakobson's model in learning ma'ani science, a branch of balaghah science that studies the meaning and structure of language in the context of effective communication. Jakobson's model, known as the six functions of language, is seen as a relevant tool to enrich students' understanding and skills in utilizing language appropriately and effectively. A contextual approach is used to relate Jakobson's theory to everyday communication situations, so that students can more easily understand the application of ma'ani science in dynamic social, cultural and language contexts. This study suggests that by integrating Jakobson's model, teaching ma'ani science can become more interactive, relevant, and applicable, and improve students' ability to analyze and produce meaningful language. The findings are expected to contribute to the development of more innovative curriculum and methods of teaching balaghah.